Omalizumab and IgE in the Control of Severe Allergic Asthma - Gon, Yasuhiro; Maruoka, Shuichiro; Mizumura, Kenji (Frontiers in Pharmacology, 2022)
Omalizumab, a human immunoglobulin (Ig)G1 antibody against IgE, is a therapeutic agent for bronchial asthma. The Global Initiative for Asthma guidelines indicate that the use of omalizumab should be considered as an option in step 5 of treatment for patients with the most severe type of bronchial asthma. In patients with atopic asthma who are at a high risk of exacerbation, and in whom symptoms are poorly controlled despite treatment with inhaled corticosteroids, omalizumab is one of the few drugs that improves symptoms, reduces the risk of exacerbation, and improves the quality of life while offering a high level of safety. On the other hand, the associated treatment costs are high, and there are no clear methods to identify responders. A recent study suggested that evaluating the therapeutic effects and monitoring the pharmacokinetics of omalizumab could improve the success of omalizumab therapy. This review outlines the relationship between IgE-targeted therapy and the serum level of IgE to enhance the current understanding of the mechanism of omalizumab therapy. It also describes the clinical significance of measuring serum free IgE levels and monitoring omalizumab therapy.